Patients' preferences for coronary bypass grafting or staged percutaneous coronary intervention in multi‐vessel coronary artery disease. Issue 4 (9th January 2018) - Ohlow, Marc‐Alexander; Farah, Ahmed; Kuntze, Thomas; Lauer, Bernward
Summary: Background: The decision for coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) in patients with multi‐vessel coronary artery disease (mCAD) is currently made by a heart‐team approach. Patients' preference is less well investigated. Methods: All consecutive patients with prior CABG and at least 2 PCI procedures were interviewed whether they would elect bypass surgery or staged PCI in case of a hypothetical scenario in which they had mCAD and CABG or PCI will equally improve symptoms and survival. Results: A total 213 patients were surveyed. About 21 (10%) patients had multiple CABG, and mean number of PCI per patient was 4.0 ± 2.7. Complications during CABG were reported in 19.7% and in 14% after PCI, respectively. About 15% experienced complications after both CABG and PCI, and 51% had no complications at all. Mean symptom‐free period was 5.2 (following CABG) vs 1.8 years (following PCI); P <.001. Duration of recovery was significant shorter after PCI (mean 9.2 ± 1.2 vs 136.4 ± 57.9 days; P <.01). Based on their personal experience with both procedures, 15% of the participants elected CABG in the hypothetical scenario and 67% choose staged PCI, 18% were equally happy with either. More participants preferred PCI when age was ≥70, complications following CABG occurred, and when undergoing CABG first. Gender, number of CABG or PCI procedures per patient, and complications following PCI did not affect participants' preference. Conclusions: In our hypothetical scenario, the majority of participants preferred staged PCI over CABG. Preferences were related to age, complications following CABG, and whether CABG was performed first.